Dietary selenium excess affected spermatogenesis via DNA damage and telomere-related cell senescence and apoptosis in mice. (January 2023) - Zhang, Yue; Liu, Jianhui; Li, Xiangyang; Zhou, Guiqing; Sang, Yujian; Zhang, Mingyuan; Gao, Leqiang; Xue, Jinglong; Zhao, Moxuan; Yu, Huanling; Zhou, Xianqing
Abstract: Selenium (Se) is a vital microelement for spermatogenesis and male fertility. The aim of this study was to investigate the effects of Se on the male reproductive function and possible mechanisms. Fourty male mice were randomly divided into 0, 0.1, 0.3 and 0.9 mg/kg Se supplementation groups and given with Se dietary intervention for 12 weeks. Our data showed that excessive Se intake damaged the tissue structure of testes and epididymides of the mice, resulting in decreased sperm quality and quantity. Moreover, excessive Se induced oxidative stress, causing DNA damage and activated DNA damage repair factors (Mre11/Rad50/Nbs1), and also disrupted telomere function by shortening telomere length and decreasing TERT expression. Se excess activated the senescence pathway p53/p21/p16, leading to germ cell senescence, and inhibited cell proliferation by suppressing the Sirt1/Foxo1/c-Myc pathway. All of this led to spermatogenic cell apoptosis, thereby causing a decrease of sperm quantity and quality. In conclusion, excessive Se caused reproductive toxicity via inducing telomere dysfunction due to DNA damage, leading to germ cellular senescence and apoptosis in the testes of male mice. Our research provide new proof to explain the underlying mechanism of male reproductive toxicity triggered by excessive Se intake. Graphical abstract: Image 1 Highlights: Non-optimal doses of Se led to the decline of sperm quality and quantity in mice. Se excess induced DNA damage and telomere dysfunction in testis. Se excess caused cell senescence and apoptosis in testis. Se excess inhibited cell proliferation through Sirt1/Foxo1/c-Myc in testis.